The Current Reform of PRC Enterprise Income Tax Law in 2007 - Wei, Xin (2007)
China is the top fast economic growth countries in the world, which have average 7-8 percent increase in GDP every year especially after join World Trade Organization in 2001. One of the biggest and important reasons is the increase in foreign capital investment, because more and more foreign investors build their companies and factories in China which they can enjoy the lower tax rate and tax preference.